Gender stereotypes among Spanish university students about psychosocial risks in childhood - Sánchez-Sandoval, Yolanda; Vizcaya, Elena; Melero, Sandra; Verdugo, Laura (IJERI: International Journal of Educational Research and Innovation, 2019)
Recent studies have shown that gender stereotypes are not sensitive to social changes. There is a gap in how gender is treated in college. This study is part of an innovation project to improve teaching quality in university. We aim to analyze the presence of gender stereotypes related to at-risk childhood in a sample of 113 university students. Most students considered that some circumstances, like substance consumption, are more likely in boys. On the contrary, they think that looking after siblings or anxiety are more common in girls. Results show the need to incorporate the gender perspective into universities. The special needs of the at-risk girls require further research and specialized training.